Le voyage des orangers - Chiara Santini (Projets de Paysage)
The variety and the treatment of vegetables and plants are an element of a paramount importance in order to understand the classical gardens project. The flowers and the shrubs – often very rare and coming from various latitudes – used to ornate the grounds, flowerbeds and paths by embellishing the chromatic and formal palette of the compositions. This article introduces the first results of a study which has been only seldom tackled by scientific researches: the material handling of the plants aimed at decorating the royal gardens at the time of Louis XIV. The shrubs (especially the orange trees) were in fact one of the major elements for decorating these gardens. Thus, they initiated the development of specific professional skills, among the gardeners community, along with the implementation of a particularly expensive trading network; a ramified network for their spotting and their transportation to the royal plant nurseries of Ile-de-France.